The main educational approaches to the deaf: and the valorization of the culture of the deaf (Research, Society and Development, 2019)
The present research, based on bibliographical analysis, investigated the main teaching approaches and the valorization of the culture of the deaf. Oralism, Total Communication and Bilingualism are the teaching approaches that most influenced and still influence the conception of the deaf subject, sign language and deaf culture. In the oralist approach the focus was to make the students to oralize, making them look like the listeners. Sign language was strictly forbidden. Classrooms were a space for habilitation / rehabilitation for speech acquisition and lip reading, with little teaching of school content. The educational failure caused by the use of this method has generated discontent and consequently openness to the emergence of the method known as Total Communication. In this approach the student was encouraged to make use of gestures, mimics, sign languages, oralization, of hearing aids. Even though there was appreciation of the communication of these subjects, the use of this method was not enough to reverse the educational failure of the deaf students. It was from these results that the research on sign language was consolidating and giving rise to a new teaching approach known as Bilingualism. This approach argues that sign language is the first language of the deaf and its acquisition is indispensable for the construction of the identity of this subject. Thus, these discussions have as general objective to present the main teaching approaches focused on the education of the deaf and which work on valuing the culture of these subjects.